Fashion Conscious Consumption and Consumer Perception: A Study in the Local Productive Arrangement of Clothing of Pernambuco - Jordana Soares de Lira; Omero Galdino da Silva; Cristiane Salome Ribeiro Costa; Marcus Augusto Vasconcelos Araujo (BBR: Brazilian Business Review)
This study aims to analyze the relationship between the perception of corporate social responsibility actions (PCSRA) and the purchase of green products (PGP) on price sensitivity (PS) and the influence of these constructs on conscious consumption (CC). For this purpose, a descriptive quantitative study was carried out with fashion consumers of a Local Productive Clothing Arrangement in the Agreste area of Pernambuco, and the data was analyzed using Structural Equation Modeling. The results identified that PGP has an influence on PS and a negative relationship with CC. PCSRA, on the other hand, has a positive influence on CC, but not on PS, and the relationship between PS and CC was not significant. These results indicate that social aspects have a greater predominance over CC, and price does not seem to be a barrier to the consumer’s consciousness regarding the consumption of fashion products. This study innovates by bringing to debate the relationship between relevant constructs that have been investigated separately in the field of consumption.